The Production of Enzyme Bio-Cleaner Using Lemon, Lime and Pineapple through Fermentation Process - Nuramirah,; Mohd Lazim, Nurul Fatin Hidayah; Mohd Adan, Nurul Husna; Ahmad Nordin, Norain (Multidisciplinary Applied Research and Innovation, 2020)
Enzyme bio-cleaner is a natural cleaning agent that contains specific quantities and qualities of bacteria along with enzymes and microbial nutrients that essentially digest chemical and organic waste. The bacteria consumed by this cleaners are converted into two basic compounds which is carbon dioxide and water. Based on past research, some of organic waste that have been used to produce enzyme bio-cleaner were orange and pineapple compared to other fruit waste. The main goal of this research is to produce a natural cleaning agent from citrus fruit using a different rate of acidity which is lemon, lime and pineapple through fermentation method. The waste of this fruits was prepared by cutting and washing using ionized water. 500 ml of ionized water was mixed with 50g of sugar solution and 150g of fruit waste. This solution was leave at room temperature for 30, 45, and 60 days. The fermentation was done after the solution filtered and analysed using Refractometer HI97801 Digital Brix and Benchop Meter HQ440d. The effectiveness of enzyme bio-cleaner of lemon, lime and pineapple were found to be 3.84 pH, 4.02 pH and 4.28 pH. The results indicated that lemon waste showed the most effectiveness among the 3 fruits waste.